2011
DOI: 10.1016/j.jvs.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Knitted nitinol represents a new generation of constrictive external vein graft meshes

Abstract: Combining the suppression of intimal hyperplasia with a more physiologic remodeling process of the media, manifold higher kink-resistance, and lower fraying than in braided meshes makes knitted nitinol an attractive concept in external vein graft protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
(41 reference statements)
0
27
1
Order By: Relevance
“…Additionally, the authors demonstrated that only in the 50% constricted vein graft was endothelialization maintained (Zilla et al, 2008). Although the authors demonstrated some pulse compliance in a subsequent knitted nitinol wire mesh study, wire breakage and www.frontiersin.org a lower degree of surface endothelialization was observed (Zilla et al, 2011).…”
Section: Autologous Graftsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the authors demonstrated that only in the 50% constricted vein graft was endothelialization maintained (Zilla et al, 2008). Although the authors demonstrated some pulse compliance in a subsequent knitted nitinol wire mesh study, wire breakage and www.frontiersin.org a lower degree of surface endothelialization was observed (Zilla et al, 2011).…”
Section: Autologous Graftsmentioning
confidence: 97%
“…Despite the decreased intimal hyperplasia observed with the supported vein grafts, the wire mesh supports are not biodegradable and thus, introduce the risk of future complications (Vijayan et al, 2004) should the wire supports fray, break, or undergo radial narrowing from axial distension (Zilla et al, 2008(Zilla et al, , 2011. Vijayan et al examined a polyglactin biodegradable external sheath as support for porcine saphenous vein grafts to prevent future risks from permanent stents.…”
Section: Autologous Graftsmentioning
confidence: 99%
“…[20][21][22][23] Recently, perivenous mesh was proposed as a promising structural design following extensive evaluations. [16][17][18]33,34 The optimal balance between ultrastructural porosity and mechanical resistance of meshes requires further investigation. A pioneer study by van der Merwe and colleagues 35 has provided a numerical approach to optimization of constrictive knitted meshes.…”
Section: Ultrastructure Of External Supporting Materialsmentioning
confidence: 99%
“…Type of external support Animal model Result Barra 12 Constrictive (low Qc) Dacron mesh Sheep carotid artery interposition graft Positive EI-Kurdi 15 Microfibrillar polymer Porcine carotid artery interposition graft Positive Zilla 16,18,34 Nitinol mesh Chasma baboon femoral artery interposition graft Positive Lardenoye 24 Polyethylene Transgenic mouse carotid artery interposition graft Positive Izzat 31 Constrictive (high Qc) Polypropylene Porcine: carotid artery interposition graft Negative Mehta 6 Loose-fitting (high Qc) Polyester Porcine carotid artery interposition graft Positive Vijavan 19 Polyglactin Porcine carotid artery interposition graft Positive George 20 Polyester and PTFE Porcine carotid artery interposition graft Positive Jeremy 21,22 Polyester and polyglactin Porcine carotid artery interposition graft Positive Izzat 31 Polypropylene Porcine carotid artery interposition graft Positive Angelini 23 Polyester Porcine carotid artery interposition graft Positive You 32 Polydioxan Rabbit carotid artery interposition graft Positive Qc: quotient of cross-sectional areas of the recipient arteries to in situ (pre-harvest) vein grafts.…”
Section: Authormentioning
confidence: 99%
“…Knit structures are flexible and highly porous and have an inherent ability to resist unraveling when cut. Due to the high level of conformability and porosity, knitted fabrics are ideal candidates for vascular implants 37 . Other applications include aortic valves, 38 tracheal cartilage reconstruction 39 and ligament reconstruction 40 .…”
Section: Introduction: Techniques For Preparation Of Porous Structurementioning
confidence: 99%